Review of the state of the art of mental health financing in Brazil - Costa, Emanuely Silva; Freitas, Vitor Eduardo Veras de Sandes (Argumentum, 2025)
This study analysed the current state of scientific output on mental health financing in Brazil. It employs a qualitative approach, with secondary quantitative data, based on a survey of the Scielo, Periódico Capes, ARCA, Lilacs, ScienceDirect and PUBMED databases, from 2002 to 2024. The descriptors were: financing and mental health. Using a mixed-methods approach, eight relevant studies were selected from a total of 2,277, with an average output of 0.3 per year. The results indicated restricted output in this area, and limited future prospects of investigating the effectiveness of policy and improving its control mechanisms. It did not identify a theoretical line of work in the studies covered, suggesting that there is a theoretical shortfall in the investigation of funding for mental health.